Sustainable Economy-Based Management of Tofu Industry Waste in Agrarian Areas - Qurrotun Nada Maulidia; Nafhatin; Agung Dwi Bahtiar El Rizaq (Program Studi Pendidikan IPS Unesa, 2025)
This study focuses on the sustainable economy-based management of tofu industry waste in Teja Timur Village, Pamekasan, with an emphasis on applying circular economy principles through community empowerment. The study employed a descriptive qualitative method, with data collected through in-depth interviews, direct observation, and documentation. The research instruments consisted of semi-structured interview guidelines and observation sheets. Data were analyzed thematically through the stages of data reduction, data display, and conclusion drawing. To strengthen validity, the study involved seven informants selected based on specific criteria, including tofu industry owners, workers, and community members engaged in waste management. The findings indicate that local communities actively transform solid waste into economically valuable products such as tempe gembus and animal feed, contributing to increased income and strengthened local economic resilience. These practices reflect the implementation of the reduce, reuse, and recycle (3R) principles within a circular economy framework. The study recommends enhancing support for appropriate technologies, entrepreneurship training, and institutional regulation to optimize and sustain this waste management system.